Mega web development bootcamp with React Bootstrap 5, Redux, and REST API. (Packt Publishing, 2023)
In this course, we will explore the intricacies of Redux state management, leveraging the power of the Context API to dynamically control functionality based on user sessions. To kickstart, we will establish our local development environment, installing the VS Code and NodeJS runtime. By harnessing the power of GET, POST, PUT, and DELETE endpoints, you will gain hands-on experience in consuming APIs and performing various operations. Then, we will create our first React app and dive deep into understanding the inner workings of application creation. To elevate the aesthetics of our websites, we will integrate Bootstrap 5, FontAwesome, Google Fonts, and essential NPM packages into our ReactJs projects. Our website will feature a visually appealing navigation bar, a captivating hero section with carousel and slider components, engaging sections for featured and latest posts, a compelling call-to-action segment, a portfolio showcase, and user-friendly contact and about pages. Additionally, we will implement essential functionalities such as creating, updating, and deleting posts, user login and signup capabilities, dynamic navigation, and integration with Redux and Context API for efficient state management. By the end of the course, you will have mastered the art of frontend development with modern web technologies, empowering you to confidently create professional and captivating websites. What You Will Learn Learn about Bootstrap 5 and how to use different Bootstrap CSS classes Gain insights into ReactJS project organization and optimize performance Learn to integrate GET, POST, PUT, DELETE REST APIs with React app Study Redux state management and Context API, and how to use them together Understand how to use Google Fonts and Font Awesome Icons Study and implement the Responsive Web Development Audience This course is ideal for a frontend developer, UI/UX developer, React developer, web application developer, or frontend engineer. This course provides the essential skills and knowledge to excel in the field of web development. It is also well-suited for anyone who desires to become a job-ready frontend developer proficient in ReactJs, Redux, Bootstrap 5, and API integration. Basic knowledge of HTML is recommended as a prerequisite for this course, ensuring that learners can fully leverage the concepts and techniques taught throughout the program. About The Author Ranjan Pandey: Ranjan Pandey is a full-stack DevOps software professional with over 11 years of experience in a variety of technologies ranging from web and mobile application development using HTML5, CSS3, JavaScript, jQuery, Bootstrap, Angular, React, Java, Spring, Spring Boot, Python, Flask, Django, NodeJS, Express, Android, Ionic, React Native, Flutter to artificial intelligence and cloud technologies such as Amazon Web Services and Microsoft Azure. He is a certified professional in Java, Azure Cloud, and Backbase products and has experience working with multiple MNCs and European clients. He is also a corporate trainer providing a wide range of training.